Beyond simple T/V distinctions: Investigating Balti personal pronouns as markers of social distance, authority, and communal solidarity - Zulfiqar Ali; Muhammad Mustafa; Dr. Muhammad Essa (Yayasan Mitra Persada Nusantara, 2026)
The study was aimed at examining the sociolinguistic role of the pronouns in the Balti language and how they are used to express power and solidarity relations within the Balti community in Baltistan. Using the theoretical framework of Brown and Gilman (1960), this qualitative study uses a purposive sampling technique, whereby it applied of semi-structured interviews and observation data collected among native speakers (Balti Poets). It is in the analysis of specific variants of pronouns, including formal and informal pronoun forms of